The collective farm experimental work of Dnipropetrovsk region (based on journal «In aid of houses-laboratories») - S. D. Kovalenko (History of science and technology, 2016)
The article deals with the development of collective farm experimental work in Dnipropetrovsk region using monthly science-popular methodical journal «In aid of houses-laboratories»- printed organ of local importance, performed a number of functions for the proper development of collective farm experimental work and highlight the best results of the main pressing agricultural issues, that were in the responsibility of houses-laboratories. The attention is focused on the activity of journal during 1936-1937 years. Here is conducted the content analysis of publication numbers of journal and determined its range of problems.